Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae) - Fateryga, Alexander V. (Zootaxa, 2020)
Nesting of Stenancistrocerus obstrictus was studied in the Republic of Dagestan, Russia. Ten nests were observed, six of them were dissected and their structure was studied. The nests were located in preexisting holes in a clayey cliff. Females searched for a place for the nest during more than a day. The holes with nests were 2.5–10.5 cm in length and 3–4 mm in diameter. Nest entrances were surmounted by laced earthen turrets curved downwards. The maximum length of a turret was 2 cm; the turrets had more laced structure at their distal ends while they became more solid towards the base. Nests consisted of a row of 3–10 cells separated by thin mud partitions. The cells were 5–9 mm in length. All lateral walls of the cells, as well as the vestibular cell were lined with a thin layer of mud. Females collected the building material outside the nests; they mixed clayey earth with regurgitated liquid and formed mud pellets used for the nest construction. Complete nests were sealed by final plugs; their turrets were dismantled by the females. The provision was tiny larvae of an unidentified curculionid beetle; several dozens of them were stored per cell. No parasites and associates were found in the nests. Reproductive success amounted to 92%. Adult feeding was recorded on flowers of Tamarix hohenackeri. The species is univoltine; hibernation occurs at the prepupa stage. Adult wasps are active from the end of May to the end of July. Nesting biology of the genus Stenancistrocerus and its phylogenetic position are discussed. Such a type of the nesting could be regarded as intermediate between nesting in various preexisting cavities and the excavation of burrows in an earthen substrate. The distribution of S. obstrictus is summarized; it includes Russia (Astrakhan Prov., Kalmykia, Stavropol Terr., Dagestan), Armenia, and Azerbaijan; the presence of the species in Eastern Europe is confirmed. The lectotype of Odynerus obstrictus Morawitz, 1895 is designated.